Study on the associations between liver damage and antituberculosis drug rifampicin and relative metabolic enzyme gene polymorphisms. Issue 2 (20th December 2021) - Su, Qiang; Liu, Qiao; Liu, Juan; Fu, Lingyun; Liu, Tao; Liang, Jing; Peng, Hong; Pan, Xue
ABSTRACT: The occurrence of antituberculosis drug-induced liver injury affects the effectiveness of antituberculosis treatments. Understanding the mechanism and risk factors of such liver injury may improve the outcomes of those patients who received antituberculosis treatments. In this study, 2, 255 pulmonary tuberculosis patients were included. Their medical records were reviewed, questionnaire surveys, liver function tests at the end of February (including patients with uncomfortable symptoms during the intensive treatment period), and blood samples were saved. Afterward, cases of liver damage were determined using Chinese liver damage criteria. The genotype of all participants was determined using the PCR-LDR method. Finally, the association between genetic polymorphism and ATB-DILI susceptibility was assessed using the univariate Logistic regression models. Among the 2, 255 tuberculosis patients who received rifampicin, 612 (27.1%) had antituberculosis drug-induced liver injury. We observed higher proportions of older age, male, and lower levels of AST, ALT, and TBil among patients with liver injury. Results of univariate of logistic regression models showed that patients with CYP2C19 were more likely to have liver injury compared with no such genotypes patients (all P < 0.05). Patients with tuberculosis with older age and genetic polymorphism of CYP3A4, CYP2C9, and CYP2C19 who received long-term rifampicin treatment were more likely to have antituberculosis drug-induced liver injury. It is important for healthcare providers to carefully evaluate and monitor rifampicin use for these patients.